Literature Review: Impact of Mentoring and Training on Improving the Quality of Nursing Care Documentation - Yuli Triwulandari; Dyah Wiji Puspita Sari; Muh. Abdurrouf; Nopi Nur Khasanah (Indonesian Journal of Global Health Research, 2025)
Quality nursing care documentation is essential to support patient safety, continuity of care, and legal aspects of nursing practice. Mentoring and training are effective strategies to improve nurses' knowledge, skills, and compliance in documenting nursing care accurately and systematically.Objectives: This study aims to analyze the impact of mentoring and training on improving the quality of nursing care documentation. Methods: This study used a literature study approach by reviewing national and international articles published in the period 2019-2025. The articles selected were full-text and open access scientific publications. Literature sources were obtained from three main databases, namely Google Scholar, PubMed, and SciSpace. The search strategy used the PICO (Population, Intervention, Comparison, Outcome) framework with keywords such as "mentoring", "training", "documentation quality", and "nursing care", resulting in 534 articles. The article analysis process followed the PRISMA flow. At the initial stage, duplication was eliminated, leaving 127 articles. Further screening excluded 92 articles that were not relevant or did not meet the inclusion criteria. The remaining 35 articles were screened for eligibility by considering the focus of mentoring and training interventions on nursing documentation. After this stage, only 10 articles met all criteria and were further analyzed in this review. Results: showed that structured mentoring with clear objectives, case-based training, utilization of technology, as well as management support contributed significantly in improving the completeness, accuracy, and consistency of documentation.